STEM in physics learning: Benefits, challenges, and future research opportunities - Saripah, Siti Awaliyah; Wibowo, Firmanul Catur; Astra, I Made; Budi, Esmar (Momentum: Physics Education Journal, 2025)
Data-driven approaches have emerged for several reasons, including the continuous evolution of the education sector. Across various educational fields and levels, STEM integration in learning has been implemented. Therefore, this journal presents data on the role of STEM in Physics Education. The research discussion on the use of STEM in Physics learning can also serve as a coherent background and literature review for readers who wish to conduct further research. The literature review is conducted by considering the bibliometric perspective of publications related to STEM integration in Physics learning. This study supports the journal's importance by highlighting the need for reputable journal publications. The analysis aims to provide a comprehensive bibliography and review of STEM's use in Physics learning, utilizing the "Bibliophagy" function within the "bibliometric" package of R-studio. A total of 880 papers, published between 2014 and 2025, were reviewed. This study provides perspectives, namely a general overview, annual publication numbers, prominent authors, institutions with the highest citations per document, and countries with the highest productivity. This analysis generates journals, highly cited authors, reference networks, and groups with significant contributions to the literature. This journal can be used to improve the understanding of readers or future researchers regarding global research, identify research gaps, and support further research in this field.